Stolen Honor: Stigmatizing Muslim Men in Berlin by Katherine Pratt Ewing (Stanford: Stanford University Press, 2008. 282 pages.) (American Journal of Islam and Society, 2009)
With Stolen Honor: Stigmatizing Muslim Men in Berlin, anthropologistKatherine Ewing has made a timely and valuable contribution to the literatureon Muslims in Europe. Ewing explores the stigmatization of Muslimsof Turkish origin in light of multiple societal controversies ranging fromhonor killings to citizenship tests meant to determine who can belong to theGerman nation.While the focus in both the popularmedia and social scienceliterature has typically been on Muslim women in western societies, StolenHonor offers a novel perspective on men, who are usually overlooked bysocial scientists and demonized by the media ...